Propionic Acidemia: Diagnosis and Neuroimaging Findings of This Neurometabolic Disorder - KARIMZADEH, Parvaneh (Shahid Beheshti University of Medical Sciences, 2014)
OBJECTIVE: Propionic acidemia is one of the rare congenital neurometabolic disorders with autosomal recessive inheritance. This disorder is caused by a defect in the propionyl-CoA carboxylase enzyme and can be presented with life-threatening ketoacidosis, lethargy, failure to thrive, and developmental delay. MATERIALS & METHODS: The patients diagnosed as having propionic acidemia in Neurology Department of Mofid Children’s Hospital in Tehran, Iran, between 2002 and 2012 were include in our study. This disorder was confirmed by clinical manifestations, neuroimaging findings, and neurometabolic assessment in the reference laboratory in Germany. Our study was conducted to define the sex, age, gender, past medical history, developmental status, clinical findings, and neuroimaging manifestations in 10 patients with propionic acidemia. RESULTS: Seventy percent of patients were offspring of consanguineous marriages. In this study, only one patient had microcephaly at birth, but at detection time, 30% of patients had head circumference and weight below the 3rd percentile. The patients were followed for approximately 5 years and this follow-up showed that the patients with early diagnosis had a more favorable clinical response. Neuroimaging findings included brain atrophy, white matter and globus pallidus involvement. CONCLUSION: Finally we suggest that early diagnosis and treatment have an important role in the prevention of disease progression.